Perburuan Paus di Antartika: (Australia Melawan Jepang: Intervensi Selandia Baru) - Tasya Ester Loijens (CV Rewang Rencang, 2020)
In the case of whaling in Antarctica proposed by the State of Australia, the ICJ is faced with a very technical problem related to the interpretation and assessment of elements of a scientific nature. The court evaluated claims from Australia that Japan through a whaling program called JARPA II concealed commercial purposes behind false scientific research. This case then brought the world's attention in the international agenda, especially the correlation between law and science. On the other hand, the ICJ has also come under criticism for handling cases of a technical nature, so questions arise with regard to the jurisdiction of the International Court of Justice in handling the complexity of factual issues in a healthy and fair manner. Essentially, the ICJ should avoid two major hurdles: limiting judgment to only legal aspects or becoming a science judge by conducting technical analsis and considering the position of previously handled cases. This interesting case will be analyzed by the author in relation to his studies in the perspective of international law.